2019
DOI: 10.1093/heapol/czz119
|View full text |Cite
|
Sign up to set email alerts
|

Access to medicines through health systems in low- and middle-income countries

Abstract: Nearly 2 billion people globally have no access to essential medicines. This means essential medicines are unavailable, unaffordable, inaccessible, unacceptable or of low quality for more than a quarter of the population worldwide. This supplement demonstrates the implications of poor medicine access and highlights recent innovations to improve access to essential medicines by presenting new research findings from low- and middle-income countries (LMICs). These studies answer key questions such as: Can perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 10 publications
1
56
0
4
Order By: Relevance
“…Our study has revealed that the COVID-19 pandemic has had a range of impacts on the care of patients with NCDs in LMICs by FLHCWs, from constraints on access to care to health effects, in particular, depression and anxiety as noted in other surveys (Ozawa et al, 2019). Despite the challenges, most FLHCWs continue to see patients either in person or remotely, the latter mode is especially common for physicians; pharmacists continue to see patients in-person.…”
Section: Discussionmentioning
confidence: 74%
“…Our study has revealed that the COVID-19 pandemic has had a range of impacts on the care of patients with NCDs in LMICs by FLHCWs, from constraints on access to care to health effects, in particular, depression and anxiety as noted in other surveys (Ozawa et al, 2019). Despite the challenges, most FLHCWs continue to see patients either in person or remotely, the latter mode is especially common for physicians; pharmacists continue to see patients in-person.…”
Section: Discussionmentioning
confidence: 74%
“…Despite years of effort there are still billions of people in LMICs, and even some in high-income countries who do not have effective access to vaccines and essential medicines that are long out of patent and can be manufactured relatively simply and cheaply. 15 We do not have any reason to expect this to be different for any vaccine or therapy developed as a result of CHIs. We also already see some state actors trying to get preferential early access to vaccines and some not engaging with international organisations and initiatives aimed at ensuring wide, equitable access.…”
Section: Chi Research Has High Social Valuementioning
confidence: 99%
“…Still, the study confirms that by enabling broader representation and perspectives at the national level, the complexity of access becomes apparent, with its priorities, trade-offs, network of global, regional and national stakeholders. This complex system approach is echoed by Ozawa et al (2019) . However, the question remains how this can be best managed.…”
Section: Discussionmentioning
confidence: 99%